Rates of turnover among general practitioners: a retrospective study of all English general practices between 2007 and 2019 - Aneez Esmail; Peter Bower; Kath Checkland; Matt Sutton; Sally J Giles; Rosa Parisi; Sharon Spooner; Yiu-Shing Lau; Jill Rubery (BMJ Open)
Objective To quantify general practitioners’ (GPs’) turnover in England between 2007 and 2019, describe trends over time, regional differences and associations with social deprivation or other practice characteristics.Design A retrospective study of annual cross-sectional data.Setting All general practices in England (8085 in 2007, 6598 in 2019).Methods We calculated turnover rates, defined as the proportion of GPs leaving a practice. Rates and their median, 25th and 75th percentiles were calculated by year and region. The proportion of practices with persistent high turnover (>10%) over consecutive years were also calculated. A negative binomial regression model assessed the association between turnover and social deprivation or other practice characteristics.Results Turnover rates increased over time. The 75th percentile in 2009 was 11%, but increased to 14% in 2019. The highest turnover rate was observed in 2013–2014, corresponding to the 75th percentile of 18.2%. Over time, regions experienced increases in turnover rates, although it varied across English regions. The proportion of practices with high (10% to 40%) turnover within a year almost doubled from 14% in 2009 to 27% in 2019. A rise in the number of practices with persistent high turnover (>10%) for at least three consecutive years was also observed, from 2.7% (2.3%–3.1%) in 2007 to 6.3% (5.7%–6.9%) in 2017. The statistical analyses revealed that practice-area deprivation was moderately associated with turnover rate, with practices in the most deprived area having higher turnover rates compared with practices in the least deprived areas (incidence rate ratios 1.09; 95% CI 1.06 to 1.13).Conclusions GP turnover has increased in the last decade nationally, with regional variability. Greater attention to GP turnover is needed, in the most deprived areas in particular, where GPs often need to deal with more complex health needs. There is a large cost associated with GP turnover and practices with very high persistent turnover need to be further researched, and the causes behind this identified, to allow support strategies and policies to be developed.